2023
DOI: 10.1097/prs.0000000000010347
|View full text |Cite
|
Sign up to set email alerts
|

“A Comparative Study of Wrap-Around versus Anterior Coverage Placement of Acellular Dermal Matrix in Prepectoral Breast Reconstruction”

Abstract: Background: Prepectoral direct-to-implant insertion (DTI) with acellular dermal matrix (ADM) is the currently preferred operation for breast reconstruction. There are different placements of ADM, which are largely classified as wraparound placement or anterior coverage placement. Because there are limited data comparing these two placements, this study aimed to compare the outcomes of these two methods. Methods: This was a retrospective study of immediate prepectoral DTI breast reconstructions performed by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…T he study "A Comparative Study of Wraparound versus Anterior Coverage Placement of Acellular Dermal Matrix in Prepectoral Breast Reconstruction," by Han et al, is a retrospective review of 159 matched patients undergoing skinsparing or nipple-sparing mastectomies; approximately half underwent reconstruction with a complete encapsulation by acellular dermal matrix (ADM) and the other half with only anterior coverage by ADM. 1 The authors found no statistical difference in seroma formation, capsular contracture rate, or total drainage. The only significant finding was a greater degree of postoperative ptosis (midclavicle-and sternal notch-to-nipple distances) in the group that had total ADM wrap (4.94%) compared with the anterior only ADM coverage (2.64%).…”
mentioning
confidence: 86%
“…T he study "A Comparative Study of Wraparound versus Anterior Coverage Placement of Acellular Dermal Matrix in Prepectoral Breast Reconstruction," by Han et al, is a retrospective review of 159 matched patients undergoing skinsparing or nipple-sparing mastectomies; approximately half underwent reconstruction with a complete encapsulation by acellular dermal matrix (ADM) and the other half with only anterior coverage by ADM. 1 The authors found no statistical difference in seroma formation, capsular contracture rate, or total drainage. The only significant finding was a greater degree of postoperative ptosis (midclavicle-and sternal notch-to-nipple distances) in the group that had total ADM wrap (4.94%) compared with the anterior only ADM coverage (2.64%).…”
mentioning
confidence: 86%
“…DTI techniques, particularly prepectoral implant placement with the use of acellular dermal matrices (ADMs), have gained popularity in recent years [11]. Prepectoral implant placement involves positioning the implant above the pectoralis major muscle, as opposed to the traditional subpectoral placement.…”
Section: Implant-based Reconstruction: Shift Towards Direct-to-implan...mentioning
confidence: 99%
“…In clinical practice, a study has reported no signi cant difference in complications between the anterior-tenting and whole-wrapping techniques. 13 However, another study has suggested that using a larger ADM, rather than a thicker one, may increase the drainage volume and duration, which could potentially increase the risk of seroma or infection. 14 However, the speci c differences between these techniques remain unclear, and the selection of the coverage method often relies on surgeons' preferences.…”
Section: Introductionmentioning
confidence: 99%